Finding initial solutions for a class of nonlinear BVP - TRÎMBIȚAȘ, Maria Gabriela; TRÎMBIȚAȘ, Radu T. (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
The purpose of these paper is to solve a nonlinear boundary value problem having the origin in fluid mechanics. The equation has in general several solutions and the main difficulty is to find starting solutions. We follow a mixed symbolic-numeric approach. Mathematics Subject Classification (2010): 65L10, 76R99.